2017
DOI: 10.1371/journal.pone.0179128
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness and plasma leptin in women with recent gestational diabetes

Abstract: Aims/HypothesisLow physical fitness (PF) is a risk factor for type 2 diabetes mellitus (T2D). Women with a history of gestational diabetes (GDM) are at risk for T2D at a young age, but the role of PF in this population is not clear. PF has also been found to correlate inversely with plasma leptin in previous studies. Here, we examine whether women who had GDM have lower PF than women after a normoglycemic pregnancy and, second, whether PF is associated with plasma leptin, independently of body fat mass.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…During pregnancy, the relevance of physical fitness has also been highlighted. Low physical fitness levels are associated with low infant birth weight, higher risk of gestational diabetes mellitus (GDM), worse postpartum recovery, and worse delivery outcomes…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During pregnancy, the relevance of physical fitness has also been highlighted. Low physical fitness levels are associated with low infant birth weight, higher risk of gestational diabetes mellitus (GDM), worse postpartum recovery, and worse delivery outcomes…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] During pregnancy, the relevance of physical fitness has also been highlighted. Low physical fitness levels are associated with low infant birth weight, 7 higher risk of gestational diabetes mellitus (GDM), 8,9 worse postpartum recovery, 10 and worse delivery outcomes. 11 Physical fitness can be divided into several health-related components: cardiorespiratory fitness (CRF), the ability to perform large muscle, dynamic, moderate-to-vigorous intensity exercise for prolonged periods of time 12 ; muscle strength, the muscle's ability to exert a maximal force on one occasion 12 ; and flexibility, the ability to move a joint through its complete range of motion 12 ; others.…”
Section: Introductionmentioning
confidence: 99%
“…A group of investigators reported lower fitness level among patients with gestational diabetes when compared with pregnant women having normal blood glucose levels. The same study found that after adjustment for BMI and body fat mass, there was a significant negative correlation between physical fitness and serum leptin level in the whole study cohort [ 15 ]. Regular exercise, which is known to increase plasma epinephrine, is necessary to achieve and maintain physical fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the maternal serum leptin levels attain peak level till the 28 th week of gestation then gradually decreases and after the delivery becomes normal due to expulsion of placenta (5). Leptin increases the body's insulin sensitivity through the regulation of insulin-mediated glucose metabolism by skeletal muscles and by hepatic regulation of gluconeogenesis (6,7). Pregnancy is associated with leptin resistance as leptin mRNA receptor is found to decrease during pregnancy.…”
Section: Introductionmentioning
confidence: 99%